Keraton Agung Sejagat dan Representasi Para Aktor Sosialnya dalam Wacana Berita di Kompas.com - Ralph Hery Budhiono (SUAR BETANG, 2020)
The appearance of some new kingdoms in Indonesia seized the public’s attention. The media then covered and published the issue to the readers. Some perspectives used in gaining and reporting the news. One of their focuses is on how to represent any social actors involved. This paper will discuss what techniques used by the writer in representing any social actors in two news articles deal with Keraton Agung Sejagat released by Kompas.com. The aim is to give a description what techniques used and its implication to the news as a whole. Critical Discourse Analysis will be the domain of the paper, meanwhile van Leeuwen’s view of social actors will be the core. This qualitative-descriptive paper is conducted in three stages, which are data providing, analysis, and the presentation of the analysis. Based on the analysis, there are eleven techniques used, i.e. exclusion, inclusion, activation, passivation, genericization, specification, individualization, assimilation, nomination, categorization, and personalization. AbstrakMunculnya beberapa “kerajaan baru” di Indonesia sempat menyita perhatian publik pada akhir 2019— awal 2020. Media massa pun berlomba meliput dan menyajikannya kepada khalayak pembaca dengan berbagai sudut pandang. Salah satu yang digunakan para penulis berita ialah representasi para aktor sosial yang terlibat dalam wacana pemberitaan itu. Makalah ini akan membahas penggunaan teknik penulis berita di media daring Kompas.com dalam merepresentasikan para aktor sosial dalam dua pemberitaan tentang Keraton Agung Sejagat. Tujuannya ialah memberikan gambaran teknik dan implikasinya terhadap pemaknaan berita. Metode analisis wacana kritis, terutama pandangan van Leeuwen tentang aktor sosial, digunakan untuk menganalisis dua pemberitaan itu. Hasilnya menunjukkan bahwa ada sebelas teknik yang digunakan penulis dalam merepresentasikan aktor sosial, yaitu eksklusi, inklusi, aktivasi, pasivasi, generalisasi, spesifikasi, nominasi, kategorisasi, dan personalisasi.